2016
DOI: 10.1007/s10877-016-9873-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delirium motoric subtypes on administrative documentation of delirium in the surgical intensive care unit

Abstract: This study compares the proportions of surgical intensive care unit (ICU) patients with delirium detected using the Confusion Assessment Method for the ICU (CAM-ICU) who received administrative documentation for delirium using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes, stratified by delirium motoric subtypes. This retrospective cohort study was conducted at a surgical ICU from 06/2012 to 05/2013. Delirium was assessed twice daily and was defined as having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 35 publications
2
41
1
1
Order By: Relevance
“…Two studies that examined ICD diagnosis codes only in patients with confirmed delirium reported sensitivity of 9% and 28% . Other studies reported sensitivity of 3–36%, specificity of 85–99%, PPV of 38–83%, and NPV of 67–90% . In our study, the same list of 32 ICD‐9 codes and related ICD‐10 codes used by Bui et al .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Two studies that examined ICD diagnosis codes only in patients with confirmed delirium reported sensitivity of 9% and 28% . Other studies reported sensitivity of 3–36%, specificity of 85–99%, PPV of 38–83%, and NPV of 67–90% . In our study, the same list of 32 ICD‐9 codes and related ICD‐10 codes used by Bui et al .…”
Section: Discussionsupporting
confidence: 58%
“…For algorithms based on ICD diagnosis codes, delirium was considered present if any of the following 32 explicit (i.e., including the term “delirium”) or implicit ICD‐9 diagnosis codes (e.g., “encephalopathy”) were used among the in‐hospital discharge codes (Table S1). In claims data from October 1, 2015, the corresponding 52 ICD‐10 diagnosis codes were used . For algorithms based on antipsychotics use, delirium was considered present if any antipsychotic drugs were used; in our study, we found that only haloperidol, olanzapine, and quetiapine had been prescribed.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…, 290.12, 290.13, 290.20, 290.3, 290.41, 290.42, 290.43, 290.8, 290.9, 293.0-293.9, 348.30, 348.31, 348.39, 349.82, 780.0, 780.09, 780.02, 780.97)[25][26][27].…”
mentioning
confidence: 99%